Mainstream consent programs for genetic counseling in cancer patients: A systematic review. Issue 3 (20th April 2020) - Scheinberg, Tahlia; Young, Alison; Woo, Henry; Goodwin, Annabel; Mahon, Kate L.; Horvath, Lisa G.
Abstract: As demand for germline genetic testing for cancer patients increases, novel methods of genetic counseling are required. One such method is the mainstream consent pathway, whereby a member of the oncology team (rather than a genetic specialist) is responsible for counseling, consenting, and arranging genetic testing for cancer patients. We systematically reviewed the literature for evidence evaluating mainstream pathways for patients with breast, ovarian, colorectal, and prostate cancer. Medline, EMBASE, and Cochrane Library were searched for studies that met inclusion and exclusion criteria. Article references were checked for additional studies. Trial databases were searched for ongoing studies. Of the 13 papers that met inclusion criteria, 11 individual study groups were identified (two study groups had two publications each). Ten of the 11 studies evaluated the acceptability, feasibility, and impact of BRCA testing for patients and/or clinicians in different clinical settings in breast and ovarian cancer, while the final study explored the attitudes of colorectal specialists toward genetic testing for colorectal cancer. None involved prostate cancer. Overall, mainstream pathways were acceptable and feasible. Medical oncologist‐ and nurse‐driven pathways were particularly successful, with both patients and clinicians satisfied with this process. Although the content of pretest counseling was less consistent compared with counseling via the traditional model, patients were largely satisfied with the education they received. Further research is required to evaluate the mainstream pathway for men with prostate cancer.